REVITALISASI NILAI KEMARITIMAN DALAM PEMBELAJARAN SEJARAH SEBAGAI UPAYA PENGUATAN KESADARAN EKOLOGIS MARITIM DALAM MENDUKUNG SDG 14 (LIFE BELOW WATER) - Levia Chessiagi; Leli Yulifar (Lambung Mangkurat University, 2026)
History education in Indonesia has not yet optimally integrated maritime perspectives, resulting in maritime values not being optimally internalized withing students’ awareness. In fact, the sea plays a fundamental role in shaping the nation’s historical identity and constitutes a strategic aspect in supporting the sustainability of marine ecosystems, as emphasized in Sustainable Development Goal (SDG) 14 (Life below Water). This study aims to analyze the revitalization of maritime values in history education as an effort to strengthen maritime ecological awareness. The research employs a qualitative approach using a literature review method by examining relevant scholarly resources. Data were analyzed though content analysis techniques to identify patterns, trends, and research gaps related to the integration of maritime values in history education. The findings indicate that curriculum and instructional practices of history education have not yet optimally positioned the sea as a living space with historical, social, and ecological dimensions. The revitalization or maritime values needs to be carried out through paradigm renewal in learning, the development of contextual pedagogical strategies, and the implementation of authentic assessment. Integrating maritime values into history education has the potential; to strengthen students’ maritime ecological awareness and contribute to the achievement of SDG 14.